Effects of Ultrasound and Microwaves on Selective Reduction: Catalyst Preparation and Reactions. Issue 10 (12th August 2014) - Wu, Zhilin; Borretto, Emily; Medlock, Jonathan; Bonrath, Werner; Cravotto, Giancarlo
Abstract The reduction of organic compounds through catalytic hydrogenation is an important transformation in organic chemistry, especially in the synthesis of fine chemicals, natural products, and pharmaceuticals. This review mainly focuses on the selective reduction of substrates with multiple functional groups. Literature from the last two decades has proved the pivotal role that ultrasound and microwaves can play not only in the preparation of environmentally friendly, efficient catalysts but also in their use in catalytic reactions. Owing to the specific selective activation of the solid catalyst surface, dielectric heating and acoustic cavitation may dramatically enhance the reaction rate and selectivity. A thorough literature survey was the first step in the MAPSYN project (EU 7th Framework Program) and has the goal of the industrial demonstration of selective hydrogenations intensified by microwaves and ultrasound. Both techniques are irreplaceable tools in heterogeneous catalysis and can be expected to bring even greater success in the near future as processes are scaled up with suitable flow reactors equipped with on‐line analytical monitoring.